ANALISIS FAKTOR YANG MEMPENGARUHI REMAJA PUTRI TIDAK MENYUKAI SAYUR DAN BUAH - Kusyanti, Florentina; Sukmawati, Sukmawati (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
Food is increasingly here following the changing times which are all modern so food is also all instant, and lots of jangfoot food is very popular among teenagers. Even though instant food and jangfoot if eaten every day is not good, so less consumption of vegetables and fruit. Vegetables and fruit are very important to consume by teenagers to maintain body stamina and to overcome anemia. Vegetables and fruit are very important for teenagers, because vegetables and fruit contain lots of vitamins, fat, minerals, protein, and water. In the government program regarding the germas program, it must make people like to eat vegetables and fruit to maintain health, because vegetables and fruit are good food for the body, especially for health. The purpose of this study was to find out what factors influence adolescents not liking vegetables and fruit? qualitative research type method, the population of students is 90 people, sampling technique with purposive sampling, data analysis with univariate, results for characteristics for the age of the respondent at most is 16 years old at 43.75%. Meanwhile for teenagers who like vegetables is 79.17%, the frequency of consuming vegetables is at most 2 times at 56.25%, For teenagers who like fruit is 91.66%, for the most fruit consumption frequency is 1 times the 56,25%.